PENGUSIRAN SETAN:: SINKRONISASI IMAN, KEKUDUSAN HIDUP, DOA DAN PENGETAHUAN ALKITAB - Jonidius Illu (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Jakarta, 2020)
There is an assumption among Christians that the only ones who can do the exorcism of Satan are given special gifts from God. In addition, it has been found that some are carrying out exorcisms in ways that are contrary to the Bible. This article is written for the purpose of making Christians know that in the Bible it is explained that the status of Christians who have been saved in Jesus Christ is given the right or authority to do an exorcism of Satan. This type of research method used is qualitative research, by finding sources of reading literature also obtained data sources through observations in the field. There is also a result of them, namely the dependence of Christians on servants of God or Christians in terms of carrying out the exorcism of Satan and besides, it is found in practice that the exorcism of Satan is carried out in a way that is contrary to the Bible. The conclusion is that all Christians are given the same power or authority in carrying out the exorcism of Satan, but it cannot be done because they lack faith, do not maintain a holy life, do not pray and do not have the correct knowledge of the Bible.